Hydrothermal conversion of N-acetyl-d-glucosamine to 5-hydroxymethylfurfural using ionic liquid as a recycled catalyst in a water-dimethyl sulfoxide mixture. (10th April 2017) - Zang, Hongjun; Yu, Songbai; Yu, Pengfei; Ding, Hongying; Du, Yannan; Yang, Yuchan; Zhang, Yiwen
Abstract: Here, N -acetyl-d -glucosamine (GlcNAc), the monomer composing the second most abundant biopolymer, chitin, was efficiently converted into 5-hydroxymethylfurfural (5-HMF) using ionic liquid (IL) catalysts in a water/dimethyl sulfoxide (DMSO) mixture solvent. Various reaction parameters, including reaction temperature and time, DMSO/water mass ratios and catalyst dosage were optimized. A series of ILs with different structures were analyzed to explore their impact on GlcNAc conversion. The substrate scope was expanded from GlcNAc tod -glucosamine, chitin, chitosan and monosaccharides, although 5-HMF yields obtained from polymers and other monosaccharides were generally lower than those from GlcNAc. Moreover, the IL N-methylimidazolium hydrogen sulfate ([Hmim][HSO4 ]) exhibited the best catalyst performance (64.6% yield) when GlcNAc was dehydrated in a DMSO/water mixture at 180 °C for 6 h without the addition of extra catalysts. To summarize, these results could provide knowledge essential to the production of valuable chemicals that are derived from renewable marine resources and benefit biofuel-related applications. Graphical abstract: Highlights: Effective conversion of amino sugars to 5-HMF catalyzed by ionic liquid was realized. High 5-HMF yield of 35.8% was obtained from N -acetyl-d -glucosamine in water. The yield improved to 64.6% on using a water-dimethyl sulfoxide mixture solvent. This catalysis system can be recycled at least five times.